Proceedings of the 2009 International Workshop on Intercultural Collaboration 2009
DOI: 10.1145/1499224.1499257
|View full text |Cite
|
Sign up to set email alerts
|

Biculturals as natural bridges for intercultural communication and collaboration

Abstract: Biculturals -people who have deeply internalized more than one cultural profile -are a significant but underexplored result of globalization.This new demographic raises a number of questions for many fields that address intercultural collaboration and communication. Our research develops a theory about types of biculturals and explores the idea that these individuals possess high levels of intercultural skills and abilities that can contribute to myriad contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Cultural insiders are obvious assets to a multicultural team. Given their knowledge of and connections to other cultures present in the team, they are "natural bridges" (Brannen et al 2009) between cultures. 2 Across various contexts, researchers have found that individuals who have more connections to others are capable of shaping collective creative performance (e.g., Fleming et al 2007, Obstfeld 2005.…”
Section: Multicultural Individuals and Team Creative Performancementioning
confidence: 99%
“…Cultural insiders are obvious assets to a multicultural team. Given their knowledge of and connections to other cultures present in the team, they are "natural bridges" (Brannen et al 2009) between cultures. 2 Across various contexts, researchers have found that individuals who have more connections to others are capable of shaping collective creative performance (e.g., Fleming et al 2007, Obstfeld 2005.…”
Section: Multicultural Individuals and Team Creative Performancementioning
confidence: 99%
“…Brannen, Moore and Mughan (2013) proposed that multiculturals can act as bridges across multicultural teams to reduce the impact of faultlines. Multiculturals' greater metacognition (Brannen, Garcia, & Thomas, 2009) enables them to act as cultural bridges and enhance communication and trust in multicultural organizations (Brannen & Thomas, 2010; Hong, 2010). Since communication, collaboration, and trust facilitate knowledge transfer, multiculturals enhance organizational performance (Brannen & Thomas, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within cross-cultural management, bi-or multiculturalism has traditionally been conceived of in categorical terms of dual cultural identities, focusing on questions such as how individuals with bicultural identity can manage or switch between their multiple identities. Research has advanced from considering bicultural identity as "either/or" to "both" or "neither" (e.g., Brannen, Garcia, and Thomas 2009), where Hong and colleagues' study (2000) provides support for the "both" identity categorization with individuals switching their cultural frames depending on cues (either/or). A relational and culture-cognitive conceptualization of multiculturalism adds to these insights by explicitly conceptualizing integration, mixing, or linking of multiple cultures (L€ ucke, Kostova, and Roth 2014).…”
Section: From Categories To Cultural and Social Relationsmentioning
confidence: 99%